Metformin hydrochloride improves hepatic glucolipid metabolism in diabetes progression through SIRT5-mediated ECHA desuccinylation - Liang Tang; Qing Sun; Jinling Luo; Suying Peng (Scientific Reports)
Abstract The management of hyperglycemia and lipid metabolism is pivotal for the treatment of type 2 diabetes mellitus (T2DM). Metformin hydrochloride (DMBG) remains the most widely prescribed medication for this condition. This study aimed to elucidate the effects and underlying mechanisms by which DMBG enhances glucolipid metabolism using both in vivo and in vitro experimental models. Animal models were established using high-fat diet (HFD)-fed mice, while cellular models utilized palmitic acid (PA)-induced HepG2 cells. In vivo, the impact of DMBG on glucolipid metabolism was evaluated through measurements of insulin and HbA1c levels, intraperitoneal glucose tolerance tests (ipGTT), intraperitoneal insulin tolerance tests (ipITT), as well as histological assessments with hematoxylin-eosin (HE) and Oil-red O staining. Mitochondrial function was assessed via biochemical assays of TBARS, SOD, ATP, and H2O2 levels in liver tissue, alongside determinations of mitochondrial membrane potential, ROS production, mtDNA content, and SIRT5 mRNA expression. For in vitro analysis, glucose consumption, mitochondrial membrane potential, ROS levels, and protein expressions of AMPK and PGC-1α were quantified in HepG2 cells. Western blotting and co-immunoprecipitation (co-IP) techniques were employed to investigate the mechanistic pathways involved. Treatment with DMBG resulted in reduced levels of free fatty acids, body weight, and fat mass, while also alleviating hyperglycemia and hepatic lipid accumulation in HFD-fed mice. Furthermore, DMBG restored impaired mitochondrial function in these animals and increased SIRT5 expression via AMPK activation. In vitro, DMBG mitigated PA-induced alterations in glucose consumption and mitochondrial dysfunction in HepG2 cells, an effect that was abrogated upon SIRT5 knockdown. Overexpression of SIRT5 led to enhanced trifunctional enzyme subunit-alpha (ECHA) desuccinylation at the K540 site, thereby increasing its activity. Collectively, our findings indicate that DMBG improves hepatic glucolipid metabolism through a mechanism involving SIRT5-mediated ECHA desuccinylation, potentially offering a new therapeutic avenue for T2DM.